Analysis of serve and serve return on different surfaces in elite tennis players - Paiva de Faria Melonio, V.; Saldanha Aoki, M.; Schultz Arruda, A. F.; Souza, D.; Dário Capitani, C.; Moreira, A. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2021)
The aim of the current study was to analyze players` interactions in serve and serve return situations and examine the way points were decided due to players` positions and surfaces. Fourteen ATP 1000 tournament matches were analyzed (7 on hard surface; 7 on clay surface). The type of surface did not affect the way points ended (Chi²=9.26; p > 0.05) but did influence serve return vertical positioning (Chi²=270.86; p < 0.001). The return positioning, both lateral (Chi²=92.68; p < 0.001 on deuce side - Chi² = 78.98; p < 0.001 on advantage side) and vertical (Chi²=33.59; p < 0.001), and the type of serve (Chi²=45.13; p < 0.001) affected the way points were decided. The results from the present study suggest that tennis players should use, or at least seek, strategies based on aggressiveness and consistency of the 1st serve and also indicate that in the 2nd serve return, players are more offensive, and that on hard surfaces, players stand a few steps inside the court to return the serve, differently from clay surfaces. It recommended that serve returns should combine aggression, by inside the court positioning, and accuracy.